Lawless zones, rightless subjects: migration, asylum, and shifting borders - Benhabib, Seyla; Shachar, Ayelet (Cambridge University Press, 2025)
Responding to ever-increasing pressures of migration, states, supranational, and subnational actors deploy complex moves and maneuvers to reconfigure borders, rights, and territory, giving rise to a changing legal cartography of international relations and international law. The purpose of this volume is to study this new reconfiguration of rights, territoriality, and jurisdiction at the empirical and normative levels and to examine its implications for the future of democratic governance within and across borders. Written by a diverse and accomplished group of scholars, the chapters in this volume employ legal, historical, philosophical, critical, discursive, and postcolonial perspectives to explore how the territoriality of the modern states - ostensibly, the most stable and unquestionable element undergirding the current international system - has been rewritten and dramatically reimagined. This title is also available as Open Access on Cambridge Core.